1991
DOI: 10.1007/bf00982132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of floral compounds fromAbelia grandiflora that stimulate upwind flight in cabbage looper moths

Abstract: Four major volatile components emitted from flowers ofAbelia grandiflora were identified based on retention time using two capillary columns of different polarities and electron impact mass spectrometry. These are phenylacetaldehyde, benzaldehyde, 2-phenylethanol, and benzyl alcohol. A blend of these compounds was as effective as a cluster of flowers in stimulating upwind flight by maleTrichoplusia ni to the source in a wind-tunnel test. Phenylacetaldehyde or 2-phenylethanol were each as effective as the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 19 publications
4
83
0
3
Order By: Relevance
“…different shape of traps and flowers, may also have reduced the trap catches. Phenylacetaldehyde, the most attractive scent in our study, has been reported earlier as an attractant for diurnal and nocturnal Lepidoptera (Creighton et al 1973;Cantello and Jakobson 1979;Haynes et al 1991;Heath et al 1992;Honda et al 1998;Andersson and Dobson 2003) and honeybees (Blight et al 1997). Andersson et al (2002) describes phenylacetaldehyde as a characteristic compound of butterflypollinated flowers because of its widespread occurrence in such plants, but the compound has also been found in many other plants (Knudsen et al 1993).…”
Section: Behaviourally Active Fragrancessupporting
confidence: 70%
“…different shape of traps and flowers, may also have reduced the trap catches. Phenylacetaldehyde, the most attractive scent in our study, has been reported earlier as an attractant for diurnal and nocturnal Lepidoptera (Creighton et al 1973;Cantello and Jakobson 1979;Haynes et al 1991;Heath et al 1992;Honda et al 1998;Andersson and Dobson 2003) and honeybees (Blight et al 1997). Andersson et al (2002) describes phenylacetaldehyde as a characteristic compound of butterflypollinated flowers because of its widespread occurrence in such plants, but the compound has also been found in many other plants (Knudsen et al 1993).…”
Section: Behaviourally Active Fragrancessupporting
confidence: 70%
“…It has been described as an attractant for the green lacewing Chrysoperla carnea Say (Neuroptera: Chrysopidae) (Zhu et al, 2005), several beetles (Dickens, 2006, Zhu et al, 1999, flies (Chapman et al, 1998;Ishikawa et al, 1983) and moths (Haynes et al, 1991). Among scarabs, it attracts Hoplia communis Waterhouse (Coleoptera: Scarabaeidae, Hoplinae) (Imai et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Today, many aromatics are used as Lepidoptera attractants. For example, a mixture of benzaldehyde, phenylacetaldehyde, 2-phenylethanol and benzyl alcohol, which was released from Abelia grandiflora [22] flowers, was a strong attractant for Trichoplusia ni moths. Heath et al [23] also reported that electrophysiological responses of Trichoplusia ni to phenylacetaldehyde were equal to responses from a mixture of benzaldehyde, benzyl acetate and phenylacetaldehyde.…”
Section: Discussionmentioning
confidence: 99%